Microscope as Absorbance Reader with Utility in Clinical Analysis - Orlando-Guerrero, I. J.; Bravo-Delgado, C. H.; Hernández-Paxtián, Z. J.; Aguilar-Felipe, A. A (Revista Mexicana de Ingenieria Biomedica, 2018)
The decentralization of clinical laboratories is under development, which has led to the design of instruments that offer fast, reliable and patient-side results, this trend is known as point of core testing (POCT) and It offers the pos-sibility of giving an immediate follow-up to the disease. The objective of this investigation was the implementation of an absorbance meter, using the structure of an optical microscope, to which a light filter and a digital camera have been adapted. This allows to obtain values of average intensity of solid images of enzymatic reactions, and from them to estimate absorbance or concentration. As results, we present absorbance calibration lines and concentra-tion measurements for cases of gentian violet, a glucose oxidase kit and samples of volunteer patients. We conclude that there is a measurement error of less than ± 1mg / dl compared with the measurements of an Elisa plate reader and a semi-automated blood chemistry analyzer. Taking into account the above, the system turns out to be a viable alternative for estimating absorbance and increasing the functionality of optical microscopes in health clinics.